The role of culture economics in social health: the case of cultural diversity in Iran - Narges Soltanizadeh; Sousan Alaei (Shahid Beheshti University of Medical Sciences, 2016)
Background: The culture economy usually deals with the economy in the field of art and culture, and due to the cultural diversity in Iran, its effects on the social health have always been controversial. The purpose of this study was to determine the role of the cultural economy on social health with respect to cultural diversity in Iran. Methods: A comprehensive search had been done in the following databases: web of science, PubMed, SciVerse Scopus, Google scholar and MEDLINE, using keywords including, culture economics, social health, and cultural diversity. Library research was carried out either. A total of 48 articles related to the topic of the study were found. Among them, 24 articles were found to be precisely related to the topic of the study. Findings were criticized and analyzed. Results: The economy of society could be affected by any changes in culture. On the other hand, cultural diversity also obviously affects the various aspects of mental health, including health and disease perceptions, coping styles, treatment patterns, the impact of history, racism, bias and stereotypes, gender and family, shame and discrimination. Cultural diversity provides many opportunities for working in a unique and effective way in the field of positive mental health. Conclusion: If the economy of society moves on the basis of the development of profit and social capital, it will create a context for growth and development of culture. Cultural diversity is also in line with the economics of culture as a motivating factor for the development not, only in the economic arena but also in the expansion of intellectual and creative spheres and social health.